Implementasi Sistem Penjaminan Mutu Internal Dalam Meningkatkan Kualitas Pembelajaran di Madrasah Ibtidaiyah Negeri 4 Batanghari - Amrizal; Pranata, Agus; Miranda, Dira Ayu; Yunita, Fitri Rahma; Sukatin (LEMBAGA PENELITIAN & PENGABDIAN MASYARAKAT UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
This research aims to determine the extent to which the implementation of the education quality management system is based on internal management quality standards at Madrasah Ibtidaiyah Negeri 4 Batang Hari in developing improved learning processes. This research is descriptive research whose data collection method uses observation and interviews. The sample of this research is school principals. The results of this research show the level/percentage of achievement of the implementation of internal quality assurance management which includes aspects of the observation and documentation system. Keywords: Learning Quality, Internal Quality Assurance System